Study of the mutual connections among information-communication technologies, organisational learning and business performance - Miha Skerlavaj; Vlado Dimovski (Journal for East European Management Studies, 2006)
This paper presents the results of a study (involving 220 larger Slovenian companies) which aimed to examine the influence of information and communication technologies (ICT) and organisational learning (OL) on both financial (FP) and non-financial performance (NFP). In this manner a structural equation model was conceptualised based on prior theoretical and empirical foundations. According to responses from Slovenian CEOs, the statistically significant and positive influence of ICT on FP and NFP were established. No support for the ICT productivity paradox can be provided by our research. Future longitudinal research needs to establish whether the ICT productivity paradox is the reverse image of organisational learning. – – Der Aufsatz präsentiert die Ergebnisse einer Studie (von 220 größeren slowenischen Firmen), die darauf abzielt, den Einfluss von Informations- und Kommunikationstechnologien und organisatorischem Lernen auf den finanziellen und auch nichtfinanziellen Erfolg zu untersuchen. Somit wurde ein strukturelles Modell konzeptualisisiert, das auf früheren theoretischen und empirischen Annahmen fundiert. Anhand von Antworten slowenischer Führungskräfte wurden statistisch wichtige und positive Einflüsse der Technologien auf die betreffenden Kriterien erfaßt. Die Technologien haben jedoch keinen statistisch wichtigen Eindruck auf den nichtfinanziellen Erfolg. Zukünftige Forschung ist nötig, um darzustellen, ob das ICT Produktivitätsparadoxon das umgekehrte Abbild vom organisatorischem Lernen ist.
Keywords: 650; Organisational learning; information-communication technologies; productivity paradox; organisational performance; Slovenia